Der Passauer Vertrag (1552): Einleitung und Edition - Drecoll, Volker Henning (Arbeiten zur Kirchengeschichte, 2000)
An edition of the Treaty of Passau (1552) as well as of important protocols of negotiations, together with an extensive introduction